Review on Delivery Issues in Malaysian Traditional Ship Production Process - Jamil Haron, Surhan; Koto, Jaswar; Nofrizal, Nofrizal; Dalil, M. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
A study regarding the factor contribute toward the delivery issues of traditional ship production process in Malaysia was conducted with aims to identify the factor contributing to the issues and also offer some suggestion and recommendation to overcome the issues. This study was conducted based on literature material available from many resources such as the Malaysia timber council, journal publication, reports, magazines and other. The factors derived that can contribute to delivery of traditional ship building product are the issues of availability of the raw material, law that exist to protect the material and its trade, the production process, the issues of the worker’s skill and availability, the diminishing number of master shipbuilder and the payment methods. Some suggestion in overcoming the issues also been proposed like special permit to traditional shipbuilder for easier material obtain and the need of documentation of the traditional ship production process itself so that the actual problem existed can be further examine and solve.